2016
DOI: 10.1007/s00784-016-1752-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and imaging characteristics of palatine tonsilloliths evaluated on 2244 pairs of panoramic radiographs and CT images

Abstract: Clinicians should include tonsilloliths among the differential diagnoses when calcified bodies are detected on panoramic radiographs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
68
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(88 citation statements)
references
References 21 publications
6
68
6
Order By: Relevance
“…Tonsilloliths were detected in 300 (13.4 %) and 914 (40.7 %) of the 2244 individuals on panoramic radiographs and CT, respectively in the Takahashi et al study (15). In the present study on CBCT images, the prevalence of palatine tonsil calcifications was 20.4 %, which was higher than that reported by Aspestrand and Kolbenstvedt (16%) and lower than Fauroux et al (24.6%) on CT scans (16,17).…”
Section: Resultscontrasting
confidence: 60%
“…Tonsilloliths were detected in 300 (13.4 %) and 914 (40.7 %) of the 2244 individuals on panoramic radiographs and CT, respectively in the Takahashi et al study (15). In the present study on CBCT images, the prevalence of palatine tonsil calcifications was 20.4 %, which was higher than that reported by Aspestrand and Kolbenstvedt (16%) and lower than Fauroux et al (24.6%) on CT scans (16,17).…”
Section: Resultscontrasting
confidence: 60%
“…Comparing the number of calcifications detected, the present study showed that enhanced digital panoramic radiographs allowed for an increase in the detection of soft tissue calcification in 60.18%. This prevalence may have been different than those of other studies (Sutter et al, ; Takahashi et al, ) that assessed limited types of calcification and used non‐enhanced digital images or conventional radiographs. The present authors stated that the possibility of adjusting the image at different levels of brightness and contrast allows for the visualization of calcifications at different stages of mineralization; probably for this reason, a higher number of calcifications were detected when the images were enhanced.…”
Section: Discussioncontrasting
confidence: 57%
“…Comparing the number of calcifications detected, the present study showed that enhanced digital panoramic radiographs allowed for an increase in the detection of soft tissue calcification in 60.18%. This prevalence may have been different than those of other studies (Sutter et al, 2018;Takahashi et al, 2017) prevalence by creating false-positive. We consider that adjustments did not create a soft tissue calcification, because the examiners considered the format, aspect, and localization to classify a high-density area as soft tissue calcification and not only the density.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Smallsized tonsilloliths are usually asymptomatic, but large ones may present several symptoms such as irritation, pain, discomfort and foreign body sensation, swallowing and eating difficulties, bad breath, bad taste, ear pain, and ulceration [1,2]. Palatine tonsilloliths may cause orofacial pain and glossopharyngeal neuralgia [3]. They may be single or multiple and unilateral or bilateral [4].…”
Section: Introductionmentioning
confidence: 99%